Delta to Wye / Wye to Delta Transformation Flashcards
1
Q
Each resistor in the network is the sum of all possible products of Y resistors taken two at a time, divided by the opposite Y resistor.
A
Wye to Delta Conversion
2
Q
Each resistor in the Y network is the product of the resistors in the two adjacent branches, divided by the sum of the three resistors.
A
Delta to Wye Conversion
3
Q
Wye to Delta Conversion
A
Ra = [ R1(R2) + R2(R3) + R3(R1) ] / R1
Rb = [ R1(R2) + R2(R3) + R3(R1) ] / R2
Rc = [ R1(R2) + R2(R3) + R3(R1) ] / R3
4
Q
Delta to Wye Conversion Formula
A
R1 = RbRc / Ra + Rb + Rc
R2 = RcRa / Ra + Rb + Rc
R3 = RaRb / Ra + Rb + Rc